The Effect of the Breeder Empowerment Program on Poverty Alleviation: Case Study of Balai Ternak BAZNAS in Purworejo Regency, Central Java Province - Sudarjat, Ajat (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
Poverty in rural areas is always higher than poverty in urban areas. Therefore, poverty alleviation programs should be increased to resolve poverty in rural areas. Most of the potential resources in rural areas are in the agricultural sector, one of which is animal husbandry. The National Board of Zakat (BAZNAS) as a zakat management institution has initiated a program for utilizing zakat through empowering livestock breeders known as Balai Ternak. The research was conducted to determine the influence of Balai Ternak program in alleviating poverty. The research method was carried out by quantitative analysis of income data of 58 mustahik breeder families assisted by BAZNAS in the Balai Ternak program in Purworejo Regency, Central Java Province. Breeder income data was compared before the program and after the program. Furthermore, income after the program is compared with the Central Java Province poverty line standard, the Central Java Province had kifayah standard, and the national zakat nisab standard. The research results show that the Purworejo Regency Balai Ternak BAZNAS program was able to reduce the number of poor families by 50.0 percent. The decrease in the number of poor families was followed by an increase in the number of breeders whose income was above the kifayah limit by 41.5 percent and mustahik breeders who became muzakki by 10.3 percent.